Kajian Gamifikasi Mekanik sebagai Variabel dalam Literasi Media Board Game - Fadhilah Amalia; Alvanov Zpalanzani Mansoor (Universitas Multimedia Nusantara, 2021)
In accordance with the changes that occur in 21st century, the world’s media industry also undergoes rapid changes. The variety of media that continues to emerge and develop in all levels of society has a significant impact, one of which is the board game media. This phenomenon has attracted the attention of researchers to examine board game media as a media education towards media literacy skills. Media literacy is the ability to seek, find, and use information from media messages by adapting cognitive abilities and critical thinking in analyzing and questioning media messages that are seen, read, and watched. Media literacy has a broad scope that is believed to be able to function as the stronghold for the public in ability to think critically. This study was conducted to examine the gamification mechanics element as an independent variable in the board game media literacy, focusing on the concept of media literacy based on individual competence, especially on critical understanding criteria. Keywords: board game; critical understanding; gamification mechanics; media literacy.